The first time I saw him - Dave, Laura (Dave, Laura. Hannah Hall., 2026)
"Five years after her husband Owen disappeared, Hannah Hall and her stepdaughter Bailey have settled into a new life in Southern California. Together, they've forged a relationship with Bailey's grandfather Nicholas and are putting the past behind them. But when Owen shows up at Hannah's new exhibition, she knows that she and Bailey are in danger again. Hannah and Bailey are forced to go on the run in a relentless race to keep their past from catching up with them. As a thrilling drama unfolds, Hannah risks everything to get Bailey to safety--and finds there just might be a way back to Owen and their long-awaited second chance"--